THE TAX SYSTEM OF UKRAINE IN THE CONDITIONS OF THE FORMATION OF THE MODERN ECONOMIC MODEL - Шило, Жанна (Modern engineering and innovative technologies, 2023)
The purpose of the tax system, which is a reflection and an organic component of the country's economic model.